Exploring the integration of artificial intelligence into the teaching hospital model of journalism education in resource-constrained Zambia - Mambwe, Elastus (Frontiers in Communication, 2025)
This reflection essay explores the integration of Artificial Intelligence (AI) into the teaching hospital model of journalism education in resource-constrained Zambia. As AI transforms creativity and innovation, journalism education in low-resource contexts faces the challenge of preparing students for an AI-enhanced future amid technological limitations. Drawing on the Technology Acceptance Model, this paper argues that successful AI integration depends on faculty and students appreciating both the usefulness and accessibility of these technologies. The paper proposes reimagining journalism education through a mobile-first approach that leverages smartphone-accessible AI applications, interdisciplinary collaboration between journalism departments and technology developers to create contextually aware AI solutions, comprehensive AI literacy training, and the integration of AI tools into journalism clinics to enhance production processes. These strategies can transform resource limitations into catalysts for innovation while addressing the digital divide. The paper also emphasises that AI is not a neutral tool but a biased apparatus requiring decolonised and localised development efforts to ensure ethical and contextually relevant implementation in Global South journalism education.